2020
DOI: 10.1177/1591019920911532
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of acute ischemic stroke in patients with recurrent intracranial large vessel occlusion

Abstract: Background Data on the treatment with recurrent mechanical thrombectomy of patients with acute ischemic stroke with recurrent large vessel occlusion are limited. We report our experience with recurrent mechanical thrombectomy for recurrent large vessel occlusion. Methods During the period between May 2013 and August 2018, data on patients with recurrent large vessel occlusion were collected. Baseline clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…To date, investigations into the effect of previous stroke on thrombectomy outcomes have been limited by small sample sizes, and have reported conflicting results. When comparing outcomes between patients undergoing repeat EVT and those undergoing first time EVT, three small studies have reported similar outcomes between groups 3–6. In contrast, a retrospective analysis of EVT patients with a previous history of stroke (as opposed to only those whom underwent previous EVT) reported worse outcomes in patients with previous strokes 7…”
Section: Introductionmentioning
confidence: 99%
“…To date, investigations into the effect of previous stroke on thrombectomy outcomes have been limited by small sample sizes, and have reported conflicting results. When comparing outcomes between patients undergoing repeat EVT and those undergoing first time EVT, three small studies have reported similar outcomes between groups 3–6. In contrast, a retrospective analysis of EVT patients with a previous history of stroke (as opposed to only those whom underwent previous EVT) reported worse outcomes in patients with previous strokes 7…”
Section: Introductionmentioning
confidence: 99%